Drosophila pVALIUM10 TRiP RNAi lines cause undesired silencing of Gateway-based transgenes. - Stankovi?, D.; Csordás, G.; Uhlirova, M. (Life science alliance, 2023)
Post-transcriptional gene silencing using double-stranded RNA has revolutionized the field of functional genetics, allowing fast and easy disruption of gene function in various organisms. In Drosophila, many transgenic RNAi lines have been generated in large-scale efforts, including the Drosophila Transgenic RNAi Project (TRiP), to facilitate in vivo knockdown of virtually any Drosophila gene with spatial and temporal resolution. The available transgenic RNAi lines represent a fundamental resource for the fly community, providing an unprecedented opportunity to address a vast range of biological questions relevant to basic and biomedical research fields. However, caution should be applied regarding the efficiency and specificity of the RNAi approach. Here, we demonstrate that pVALIUM10-based RNAi lines, representing ~13% of the total TRiP collection (1,808 of 13,410 pVALIUM TRiP-based RNAi lines), cause unintended off-target silencing of transgenes expressed from Gateway destination vectors. The silencing is mediated by targeting attB1 and attB2 sequences generated via site-specific recombination and included in the transcribed mRNA. Deleting these attB sites from the Gateway expression vector prevents silencing and restores expected transgene expression.